Optimizing Self-Acceptance in the Elderly: The Influence of Islamic Guidance in Overcoming the Loss of a Life Partner - Markhamah, Muslikatul (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2024)
The aim of this journal is to increase the level of self-acceptance in the elderly group optimally by focusing on the influence of Islamic guidance in overcoming the loss of a life partner. The research method used is analysis of journal literature and trusted sources to gain an in-depth understanding of the concept of self-acceptance in the elderly, as well as the positive impact of Islamic guidance on the adjustment process after losing a partner. Through a literary synthesis, this article describes the complexity of the challenges faced by the elderly in the context of losing a life partner, and explains how Islamic values and teachings can provide meaningful spiritual and psychological support. The implications of this research underscore the importance of Islamic guidance policies in helping elderly people optimize self-acceptance after experiencing the loss of a life partner.